Evaluasi Kinerja APILL di Simpang Empat Bundaran Burung Kota Palangka Raya - Natasya, Natasya; Riani, Desi; Silitonga, Sutan Parasian (Universitas Batanghari Jambi, 2024)
Burung Roundabout is an important roundabout for mobilizing the activities of people entering and leaving the city of Palangka Raya, with the increase in population and the rise in community activities the density of vehicles also increases significantly every year. Traffic problems can occur if there is a lack of coordination in each arm of the roundabout. The research objective is to know the performance of Weaving Area and the performance of APILL at Burung Roundabout. The obtained data consists of quantitative data from field survey data. The data is analyzed using Indonesian Road Capacity Manual (MKJI, 1997). The research result using the calculations from (MKJI, 1997) for the Weaving Area section show that the maximum Capacity (C) obtained is 11,125 smp/h at the DA section. The average traffic delay at the roundabout is 0,77 second/smp with the highest delay index (DS) is 0,22 at the CD section. Consequently the service level during peak hours is classified as grade A. The analysis of APILL at Burung roundabout has good traffic flow result. The highest capacity on the southern arm is 1566 smp/hour and the highest delay is 21 second/smp. The highest queue length is 22 meters on the Southern with a highest saturation degree of 0,44 on the Southern with indicates level of service index C.